Synchrotron-based elemental mapping of single grains to investigate variable infrared-radiofluorescence emissions for luminescence dating: short communicatio - Sontag-González, Mariana; Kumar, Raju; Schwenninger, Jean-Luc; Thieme, Juergen; Kreutzer, Sebastian; Frouin, Marine (Geochronology, 2024)
During ionizing irradiation, potassium (K)-rich feldspar grains emit infrared (IR) light, which is used for infrared radiofluorescence (IR-RF) dating. The late-saturating IR-RF emission centred at ∼880 nm represents a promising tool to date Quaternary sediments. In the present work, we report the presence of individual grains in the K-feldspar density fraction displaying an aberrant IR-RF signal shape, whose combined intensity contaminates the sum signal of an aliquot composed of dozens of grains. Our experiments were carried out at the National Synchrotron Light Source (NSLS-II) at the submicron-resolution X-ray spectroscopy (SRX) beamline. We analysed coarse (>90 µm) K-feldspar-bearing grains of five samples of different ages and origin in order to characterize the composition of grains yielding the desired or contaminated IR-RF emission. Using micro-X-ray fluorescence (μ-XRF), we successfully acquired element distribution maps of up to 15 elements (<1 µm resolution) of sections of full grains previously used for IR-RF dating. In keeping with current theories of IR-RF signal production, we observed a trend between the relative proportions of Pb and Fe and the shape of the IR-RF signal, namely that most grains with the desired IR-RF signal shape had high Pb and low Fe contents. Interestingly, these grains were also defined by high Ba and low Ca contents. Our study also represents a proof of concept for mapping the oxidation states of Fe using micro-X-ray absorption near-edge structure spectroscopy (μ-XANES) on individual grains. The high spatial resolution enabled by synchrotron X-ray spectroscopy makes it a powerful tool for future experiments to elucidate long-standing issues concerning the nature and type of defect(s) associated with the main dosimetric trap in feldspar.